2009
DOI: 10.1159/000314597
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Transporter Gene Polymorphisms, Dietary Vitamin C and Serum Ascorbic Acid

Abstract: Background/Aims: Vitamin C transporter proteins SVCT1 and SVCT2 are required for the absorption and transport of vitamin C in humans. This study aims to determine whether common SVCT genotypes modify the association between dietary vitamin C and serum ascorbic acid. Methods: Non-smoking men and women (n = 1,046) aged 20–29 were participants of the Toronto Nutrigenomics and Health Study. Overnight fasting blood samples were collected to determine serum ascorbic acid concentrations by HPLC and to genotype for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 89 publications
1
42
1
1
Order By: Relevance
“…SLC23A2 rs6116569 is a tagSNP with unknown function, and in our data, it showed no detectable effect on plasma vitamin C levels. Our results showing associations between the SNP markers rs11950646, rs6053005, and rs6133175 and plasma vitamin C concentration have not been directly observed in other study populations; however, previous studies have evaluated SLC23A1 and SLC23A2 SNPs and blood vitamin C concentrations in large sample sizes (Cahill and El-Sohemy 2009;Timpson et al 2010). …”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…SLC23A2 rs6116569 is a tagSNP with unknown function, and in our data, it showed no detectable effect on plasma vitamin C levels. Our results showing associations between the SNP markers rs11950646, rs6053005, and rs6133175 and plasma vitamin C concentration have not been directly observed in other study populations; however, previous studies have evaluated SLC23A1 and SLC23A2 SNPs and blood vitamin C concentrations in large sample sizes (Cahill and El-Sohemy 2009;Timpson et al 2010). …”
Section: Discussioncontrasting
confidence: 85%
“…SLC23A1 rs4257763 is not in HapMap, but has been reported to be in partial LD with rs6596473 (for which we observed no associations) (Cahill and El-Sohemy 2009). …”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Accordingly, several variations to the status of vitamin C have been identified in several genes. A study with healthy young individuals of different ethnicities identified an association between variations in the SLC23A1 gene and circulating concentrations of ascorbic acid [24]. These findings were replicated later in a population of more than 15.000 individuals of European descent [25].…”
Section: Genetic Determinants Of Vitamin C Statusmentioning
confidence: 88%
“…These inconsistencies may be due to individual genetic variation in the serum ascorbic acid response to dietary vitamin C. In addition to Hp, other genes contain common polymorphisms that were recently shown to be potential determinants of serum ascorbic acid, including the genes that code for glutathione S-transferases (50, 51) and vitamin C transporters (52,53). An additional reason for studying these diet-gene interactions is that inconsistencies between genetic association studies, such as haptoglobin polymorphism and risk of cardiovascular outcomes in nondiabetic individuals (23), may be due, in part, to the gene-disease association being present only when a dietary factor such as vitamin C or fruit and vegetable intake is inadequate.…”
Section: Discussionmentioning
confidence: 99%